RESPITE CARE NEEDS OF INFORMAL CAREGIVERS IN CHINA: THE ROLE OF CARE NEEDS CHANGE. (16th November 2018) - Sun, Q; Lu, N; Jiang, N; Zhao, X; Lou, V
Abstract: This research examined factors associated with the intention to use respite services from the perspective of informal caregivers of elderly people, with the aim of stimulating the use of community services and bridging the gap between formal and informal care. 523 pairs of elderly people and their caregivers who successfully completed the 2013 and 2016 follow-up surveys from the Longitudinal Study on Family Caregivers for Frail Older Adults in Shanghai were included in data analysis. Two logistic regression models were adopted, with one model including factors based on the Anderson Model and the other one adding longitudinal changing factors. Results of this study indicated that the model with changing factors had greater explanatory power (R2=0.29) than the original Anderson Model on factors influencing the intention to use respite service of caregivers of the elderly people. Caregivers experiencing caregiver change (caregiver changes from son to daughter: OR=4.84, p<0.05) and taking care of elderly people with decreasing function of feeding (OR=21.83, p<0.001) but improving function of grooming (OR=4.42, p<0.05) for ADL were more likely to report their respite service needs, while caregivers caring for elderly people with more changes in number of illness (OR=0.84, p<0.05) and decreasing function of dressing (OR=0.25, p<0.05), bathing (OR=0.41, p<0.05) and bladder care (OR=0.36, p<0.05) for ADL were less likely to report their respite service needs. The identified factors associating with caregivers' respite service needs in this study provided evidence for the importance to monitor the change of care needs in community service planning and intervention.